2021
DOI: 10.3389/fimmu.2021.720952
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Immunity to Viral Infections

Abstract: The ongoing COVID-19 pandemic has increased awareness about sex-specific differences in immunity and outcomes following SARS-CoV-2 infection. Strong evidence of a male bias in COVID-19 disease severity is hypothesized to be mediated by sex differential immune responses against SARS-CoV-2. This hypothesis is based on data from other viral infections, including influenza viruses, HIV, hepatitis viruses, and others that have demonstrated sex-specific immunity to viral infections. Although males are more susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
100
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(137 citation statements)
references
References 174 publications
6
100
1
3
Order By: Relevance
“…Noteworthily, CD8+ T cells originated from females expressed a higher level of exhausted molecules (Supplementary Figure 2B), which was hardly reported before. CD4+T cells are at the core of initiating and modulating the adaptive immune responses, male-derived CD4+T cells exhibited increased immune-suppressive genes than females, like FOXP3 and IL2RA (Supplementary Figures 2C, D), in another word, more Treg cells may exist in the TME of male NSCLC patients, which is supported by several studies (37). In comparison, except for plasmacytoid dendritic cells (pDCs) showed relatively obvious sexual dimorphism (38,39), researches about the differences of myeloid cells between sexes were less characterized.…”
Section: Myeloid Cells In the Tumor Immune Microenvironment And Their Compositional Differences Between Sexessupporting
confidence: 67%
“…Noteworthily, CD8+ T cells originated from females expressed a higher level of exhausted molecules (Supplementary Figure 2B), which was hardly reported before. CD4+T cells are at the core of initiating and modulating the adaptive immune responses, male-derived CD4+T cells exhibited increased immune-suppressive genes than females, like FOXP3 and IL2RA (Supplementary Figures 2C, D), in another word, more Treg cells may exist in the TME of male NSCLC patients, which is supported by several studies (37). In comparison, except for plasmacytoid dendritic cells (pDCs) showed relatively obvious sexual dimorphism (38,39), researches about the differences of myeloid cells between sexes were less characterized.…”
Section: Myeloid Cells In the Tumor Immune Microenvironment And Their Compositional Differences Between Sexessupporting
confidence: 67%
“…While several studies reported a sex-related association of specific immunoproteasome SNPs to be associated with autoimmune-related diseases such as psoriasis or multiple sclerosis [ 60 , 61 ], the uniform reduction of all immunoproteasome and the standard β1 activity in women has not been observed before. It is feasible that this diminished proteasome function in females contributes to the well-established differences in immune responses between men and women: the generally more pronounced innate and adaptive immune responses in females contribute to faster clearing of pathogens and greater vaccination efficiency in women while—as a drawback—leading to an increased susceptibility to inflammatory and autoimmune diseases [ 62 , 63 ]. Sex-related immune regulation has been partly attributed to the differential effects of sex hormones, such as estrogen and progesterone as female, and testosterone and androgens as male sex hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Takahashi et al [14] conducted a study of patients with moderately severe COVID-19 and found that IL-8 and IL-18 levels were higher in males than in females, and that T-cell activation was stronger in females than in males. It is speculated that the decreased levels of testosterone in older males is associated with immune dysfunction, as well as the other complications of COVID-19 [15,16], whereas females have a stronger immune response based on genetic factors, such as Toll-like receptor 7 encoded in X chromosome, which might not be affected by aging or hormonal changes [17].…”
Section: Discussionmentioning
confidence: 99%